2005
DOI: 10.1111/j.1751-0813.2005.tb12203.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortalities in bobby calves associated with long distance transport

Abstract: Limits on the distance of transportation of bobby calves should be incorporated into future codes of practice to reduce the mortality of bobby calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 0 publications
1
51
1
3
Order By: Relevance
“…One of the determining risk factors is journey duration [13,14]. Consequently, Council Regulation (EC) No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the determining risk factors is journey duration [13,14]. Consequently, Council Regulation (EC) No.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the mortality due to road transport has been calculated for beef cattle in North America (0.01%) [16], fattening pigs in Europe (0.07%) [17], and bobby calves in Australia (0.64%) [13]. Whilst death is a definitive welfare outcome, the variation in the above mentioned mortality is most likely related to the species or the type of animals being transported and their transport and handling conditions [18], or else to the journey duration [14].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate for bobby calves in Australia (which has a similar industry to New Zealand) has been reported as 0.64% (Cave et al 2005) and similar levels were recorded in New Zealand (K O'Grady and R Wild, pers. comm.…”
Section: Introductionmentioning
confidence: 66%
“…Although the effect of transport duration on calf mortality has not previously been investigated, others have looked at the effect of a related variable: transport distance. In a retrospective analysis of bobby calf mortality data from Northern Victoria, Australia between 1998 and 2000, Cave et al (2005) identified an exponential increase in mortality with increasing transport distance (from farm to processor) over the range 100-800 km. Although travel duration was not known, the authors assumed that travel duration and travel distance were correlated and that distance was therefore a proxy for duration (Cave et al, 2005).…”
Section: Travel Timementioning
confidence: 99%